Cell Adhesion on Surface-Functionalized Magnesium - Wagener, Victoria; Schilling, Achim; Mainka, Astrid; Hennig, Diana; Gerum, Richard; Kelch, Marie-Luise; Keim, Simon; Fabry, Ben; Virtanen, Sannakaisa (ACS Applied Materials and Interfaces, 2016)
The biocompatibility of commercially pure magnesium-based (cp Mg) biodegradable implants is compromised of strong hydrogen evolution and surface alkalization due to high initial corrosion rates of cp Mg in the physiological environment. To mitigate this problem, the addition of corrosion-retarding alloying elements or coating of implant surfaces has been suggested. In the following work, we explored the effect of organic coatings on long-term cell growth. cp Mg was coated with aminopropyltriehtoxysilane + vitamin C (AV), carbonyldiimidazole (CDI), or stearic acid (SA). All three coatings have been previously suggested to reduce initial corrosion and to enhance protein adsorption and hence cell adhesion on magnesium surfaces. Endothelial cells (DH1+/+) and osteosarcoma cells (MG63) were cultured on coated samples for up to 20 days. To quantify Mg corrosion, electrochemical impedance spectroscopy (EIS) was measured after 1, 3, and 5 days of cell culture. We also investigated the speed of initial cell spreading after seeding using fluorescently labeled fibroblasts (NIH/3T3). Hydrogen evolution after contact with cell culture medium was markedly decreased on AV- and SA-coated Mg compared to uncoated Mg. These coatings also showed improved cell adhesion and spreading after 24 h of culture comparable to tissue-treated plastic surfaces. On AV-coated cp Mg, a confluent layer of endothelial cells formed after 5 days and remained intact for up to 20 days. Together, these data demonstrate that surface coating with AV is a viable strategy for improving long-term biocompatibility of cp Mg-based implants. EIS measurements confirmed that the presence of a confluent cell layer increased the corrosion resistance.
Keywords: cell adhesion; corrosion protection; impedance spectroscopy; magnesium; organic coating